Female Sex, Age, and Unfavorable Response to Tumor Necrosis Factor Inhibitors in Patients With Axial Spondyloarthritis: Results of Statistical and Artificial Intelligence–Based Data Analyses of a National Multicenter Prospective Registry. Issue 1 (9th December 2022) - Fernández‐Carballido, Cristina; Sanchez‐Piedra, Carlos; Valls, Raquel; Garg, Kristin; Sánchez‐Alonso, Fernando; Artigas, Laura; Mas, José Manuel; Jovaní, Vega; Manrique, Sara; Campos, Cristina; Freire, Mercedes; Martínez‐González, Olga; et al.
Abstract : Objective: Real‐world studies are needed to identify factors associated with response to biologic therapies in patients with axial spondyloarthritis (SpA). The objective was to assess sex differences in response to tumor necrosis factor inhibitors (TNFi) and to explore possible risk factors associated with TNFi efficacy. Methods: A total of 969 patients with axial SpA (315 females, 654 males) enrolled in the BIOBADASER registry (2000–2019) who initiated a TNFi (first, second, or further lines) were studied. Statistical and artificial intelligence (AI)–based data analyses were used to explore the association of sex differences and other factors to TNFi response, using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), to calculate the BASDAI50, with an improvement of at least 50% of the BASDAI score, and using the Ankylosing Spondylitis Disease Activity Score, calculated using the C‐reactive protein level (ASDAS‐CRP). Results: Females had a lower probability of reaching a BASDAI50 response with a first line TNFi treatment at the second year of follow‐up ( P  = 0.018) and a lesser reduction of the ASDAS‐CRP at this time point. The logistic regression model showed lower BASDAI50 responses to TNFi in females ( P  = 0.05). Other factors, such as older age ( P  = 0.004), were associated with unfavorable responses. The AI data analyses reinforced the idea that age at the beginning of the treatment was the main factor associated with an unfavorable response. The combination of age with other clinical characteristics (female sex or cardiovascular risk factors and events) potentially contributed to an unfavorable response to TNFi. Conclusion: In this national multicenter registry, female sex was associated with less response to a first‐line TNFi by the second year of follow‐up. A higher age at the start of the TNFi was the main factor associated with an unfavorable response to TNFi.